IDENTIFIKASI SUMBER PENCEMAR DAN TINGKAT PENCEMARAN AIR DI DANAU BATUR KABUPATEN BANGLI - CoK.I.M. HANDAYANI; I Wayan Arthana; I Nyoman Merit (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2011)
Lake Batur areas currently experiencing rapid growth with a variety of community activities. Increased community activity tends to cause pollution and disrupt the continuity of the lake water. The purpose of this study to determine the Batur Lake water quality and pollution levels. In addition to identifying sources of contaminants that exist in the vicinity of Lake Batur. Sampling was done by purposive sampling. Water samples taken at five station and at each station taken ten sub-stations that were analyzed in situ and in laboratory Lake water quality compared to quality standards in accordance with the Rules Bali Governor Number 8 of 2007. Analysis method of water pollution indexs in accordance with the Minister of Environment Number 115 in 2003. Identify source of pollution carried by record number of events, interviews and field observations. The water quality of Lake Batur showed that some parameters have exceeded the quality standard among them are BO DS (8.72 ppm), NH3 (0.86 ppm), Fe (0.61 ppm), P04 (0.36 ppm), Pb (0.04 ppm), Cu (0.70 ppm), H2S (0.007 ppm) and Cd (0.04 ppm). Water pollution index shows that the Lake Batur including light polluted with IP 1.50 to 2.82. Community activity is the source of water pollutants such as agricultural activities, settlements, tourism and fish farming activities with floating net cages (KJA). The volume of waste from the settlement activity amounted to 229,588 m3 per year and the activities of hotel and restaurant at 4595 m3 per year and the waste load of nitrogen (N) and phosphate (P) of cage culture activities amounted to 63,024 tons per year and 3372 tons per year.